Testimoni dell’agonia? La storia movimentata di un gruppo di sculture dalla cd. Sede degli Augustali (Ostia) - Bazzechi, Elisa; Danner, Marcel (Römische Mitteilungen, 2024)
This paper deals with an ensemble of eleven sculptures – mostly portrait statues – found in the so-called Sede degli Augustali at Ostia. The date and interpretation of these objects as well as their relation to the building have been discussed several times. A thorough investigation into the sculptures – which has been published alongside this paper in the database Arachne –, into their findspot, and into the excavation reports helps to establish the ‘biography’ of this ensemble: In the Imperial period, the sculptures were set up in different places such as sepulchres, houses and squares. In late antiquity, they were collected in the ‘Sede’, which was, by this time, one of the largest domus of Ostia. Finally, the sculptures were deposited and partly processed to lime in a recycling-workshop installed in the ‘Sede’.